Gynecological endoscopic society of malaysia statement and recommendations on gynecological laparoscopic surgery during COVID-19 pandemic - Wan Ahmad Hazim Wan Ghazali; Pavani Nallaluthan; Raimi Zamriah Hasan; Aizura Syafinaz Adlan; Ng Kwee Boon (Wolters Kluwer Medknow Publications, 2020)
Objectives: While the issue of aerosolization of virus from the blood occurs during usage of energy sources scare practitioners, there have been no reported instances of healthcare workers (HCWs) being infected. COVID-19 virus is primarily transmitted via respiratory droplets and contact routes. Therefore, the ultimate decision for surgery, should be based on which is the safest, quickest route and concurrently ensuring that HCWs are protected during these surgeries. During the time of crisis, HCWs need to concentrate and channel resources to the care of those affected by the coronavirus hence judicious allocation of resources is mandatory. We present the guidelines and recommendations on gynecological laparoscopic surgery during this COVID-19 outbreak in Malaysia. Materials and Methods: Thorough search of articles and recommendations were done to look into the characteristics of the virus in terms of transmission and risks during surgery. Smoke plume characteristics, composition and risk of viral transmission were also studied. Search includes The WHO Library, Cochrane Library and electronic databases (PubMed, Google scholar and Science Direct). Conclusion: We concluded that there is no scientific basis of shunning laparoscopic approach in surgical intervention. Ultimately, the guiding principles would be of reducing the anesthetic and surgical duration, the availability of full protective gear for HCWs during the surgery and the status of the patient. It is mandatory for viral swab tests to be done within the shortest window period possible, for all cases planned for surgery.